INOVASI PESANTREN KILAT RAMADHAN PADA MASA PANDEMI COVID-19 DI SMP YPPSB SANGATTA UTARA - Ifendi, Mahfud; Nafsiyah, Faizatun (STIT Ibnu Rusyd Tanah Grogot, 2023)
The COVID-19 pandemic, which has remodeled the order of human life in general, has been transformed into a new form of activity (new normal) that is different from the previous concept of life. When the holy month of Ramadan comes, it's time to increase the spiritual value of students by holding many religious activities, it is hindered by this pandemic which forbids humanity from gathering, or crowding in one place. The implementation of the Ramadhan Islamic boarding school, which in this case is one of the means to achieve the above objectives, must be conceptualized with a different pattern than before, which is done online. In this article, we describe the innovative activities that can be carried out during the implementation of Islamic boarding schools during the pandemic. By using field research, taking data by interview, observation, and documentation, and using data analysis: data condensation, data exposure, and drawing and drawing conclusions. The results of the innovation of Islamic boarding school activities during this pandemic are essentially held virtually, all of which are implemented in the form of activities in the form of reading the Qur'an, optimizing the 5 daily prayers, tarawih prayers, and suhoor suggestions, helping parents, giving charity, and Islamic seminars. The hope is that, even though it is carried out virtually, the essence, intent, and purpose of the implementation of this flash boarding school will be maintained to improve the morale and spirituality of students during the COVID-19 pandemic.